ANALISIS PENGARUH KARAKTERISTIK PENUMPANG TERHADAP PEMILIHAN MASKAPAI PENERBANGAN DI KOTA TIMIKA - Nur Hikmah; Nely Salu Padang (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
This study aims to determine the effect of the socio-economic characteristics of passengers on the choice of airlines in the city of Timika. Where in this study there were six variables including gender, type of work, income, educational status, marital status, and age. The approach used in this study is descriptive statistics in order to provide an overview or description of the object under study. There is a data analysis technique used, namely the chi square of k samples, where the chi square of k samples aims to see the relationship between each research variable and data processing using the SPSS application. The results of the test on the socio-economic characteristics of passengers carried out using the SPSS application obtained the results of the six variables where there was a very significant effect on the six variables because the calculated X^2 value > X^2 table. For the gender variable, the pearson chi square value was 11.896, then for the type of work variable, the pearson chi square value was 172,888, for the income variable the pearson chi square value was 32,924, for the educational status variable, the pearson chi square value was 12,370, while the marital status variable obtained a pearson chi square value of 80,043 and the age variable obtained a pearson chi square value of 70,420 meaning that these six variables greatly influence the choice of airlines